Pengembangan Media Rolling Ball berbantuan QR Code pada Mata Pelajaran Pendidikan Pancasila Sekolah Dasar: Penelitian - Mohamad Yahya; Rahmad Setyo Jadmiko; Diesty Hayuhantika (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research was prompted by the limited use of technology in learning media. Teachers still rely on textbooks, student worksheets (LKS), and some classic learning media. This study aims to develop Rolling Ball learning media assisted by QR Code for Pancasila Education in Class V, and to determine the validity and applicability of this media in Class V Pancasila Education. This research utilizes the ADDIE Development model, which includes Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques involved questionnaires and documentation. The subjects of this research are 25 students of class V and the class V teacher of SDN 1 Panggungrejo. The results showed that the validity level of the Rolling Ball learning media assisted by QR Code from media experts obtained a score of 97,5%, and material experts obtained a score of 81,8%. The assessment of the applicability level is taken from student questionnaires with a score of 90% and the teacher obtained a score of 97.5%. In conclusion, the Development of the Rolling Ball learning media assisted by QR Code in Pancasila Education class V of SDN 1 Panggungrejo is categorized as very good and can be applied for a more enjoyable learning process.